KANDUNGAN MERKURI (Hg) DALAM AIR LAUT, SEDIMEN, DAN JARINGAN IKAN BELANAK (Liza melinoptera) DI PERAIRAN TELUK PALU - Yusuf, Moh.; Hamzah, Baharuddin; Rahman, Nurdin (Jurnal Akademika Kimia, 2013)
Mercury (Hg) is one type of a dangerous heavy metals. As one of contaminants, mercury enter the aquatic ecosystem through atmospheric decomposition or sourced from the industrial waste externalisation and bilogical and chemical converted in methyl mercury. This research aims to find out and determine the mercury concentrate which contained in sea water, sediment and belanak (Liza melinoptera) network in Palu bay water. The analysis of mercuri content on the tested sample using Automatic Mercury Analyzer. The working principle of the device is gold amalgamation method by heating and separation. The research result showed that the mercury content in belanak network is 0.143 - 0.188 ppm, sediment is 2.453 - 2.800 ppm and the sea water is 0.030 – 0.040 ppm. Based on the decision of the state minister of environmental regarding the guidelines for determination of Hg standard quality for sea water is 0.002 ppm and 0.001 ppm for marine biota. It shows that the Palu bay water condition has been polluted and the belanak is not worth to be consumed.